Cover Image. (22nd July 2019) - Guc, Maxim; Oliva, Florian; Kondrotas, Rokas; Alcobe, Xavier; Placidi, Marcel; Pistor, Paul; Saucedo, Edgardo; Perez‐Rodriguez, Alejandro; Izquierdo‐Roca, Victor
Abstract : The front cover image is based on the Research Article CuZnInSe3 ‐based solar cells: Impact of copper concentration on vibrational and structural properties and device performance by Maxim Guc et al., https://doi.org/10.1002/pip.3150 . Design Credit: Victor Izquierdo‐Roca.